2017
DOI: 10.1097/inf.0000000000001499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Bacterial Risk Factors for Mortality in Children With Carbapenem-resistant Enterobacteriaceae Bloodstream Infections in India

Abstract: CRE BSI affects children with multiple comorbidities and repeated admissions to hospital. The mortality rate is high; combination therapy may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 37 publications
8
58
2
1
Order By: Relevance
“…The mortality we observed was lower than in both a prior series of patients with CRE BSI and a smaller case-control study of healthcare-associated infections with NDM-1 positive organisms [10,12]. Mortality was similar between patients with NDM-1 positive infections and patients with infections with other MDRO.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The mortality we observed was lower than in both a prior series of patients with CRE BSI and a smaller case-control study of healthcare-associated infections with NDM-1 positive organisms [10,12]. Mortality was similar between patients with NDM-1 positive infections and patients with infections with other MDRO.…”
Section: Discussioncontrasting
confidence: 68%
“…Prior studies of patients with CRE have identified ICU admission, prior antibiotic use and the presence of urinary and central vascular catheters as risk factors for CRE acquisition though patients with NDM-1 comprised only a small fraction of these subjects [9][10][11][12]. A significant proportion of patients with NDM-1 producing Enterobacteriaceae, however, do not have identified risk factors and appear to be community-acquired [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies comparing the outcomes for patients treated with monotherapy or combination therapy were reviewed, and control for confounders was taken into account. Most studies focused on or supplied data for BSI (212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228)(229) (Table 4), while others included other types of infection (213,215,227,(230)(231)(232)(233)(234)(235)(236) (Table 5). Systematic reviews published in 2014 found major limitations in the studies analyzed and therefore could not draw strong conclusions (47,237).…”
Section: Monotherapy Versus Combination Therapymentioning
confidence: 99%
“…The most frequent type of bacteria included were KPC-producing K. pneumoniae, although some studies included mainly OXA-48 producers (212,220,235), NDM producers (219), or noncarbapenemase producers (230). Some studies focused on specific populations, such as intensive care unit (ICU) patients (221,230), hematological or cancer patients (224, 225, 233), or children (219,232). As Tables 4 and 5 show, some studies found combination therapy to be associated with lower mortality rates, while others did not.…”
Section: Monotherapy Versus Combination Therapymentioning
confidence: 99%
“…El uso de pautas optimizadas de meropenem (a doble dosis en perfusión extendida) posibilita alcan-zar los objetivos farmacodinámicos en el caso de aislamientos con una CMI de meropenem ≤ 8 mg/L, 22 y ha demostrado una efi cacia adecuada en estudios observacionales. 23,24 Por ello, consideramos que es actualmente el tratamiento de elección en combinación con un segundo antibiótico activo in vitro. 2,25 En el caso de aislamientos con CMI de meropenem > 8 mg/L, la alternativa de elección sería un β-lactámico activo basado en los resultados del antibiograma interpretado.…”
Section: Tratamientounclassified